Chromatin Relaxation-Mediated Induction of p19INK4d Increases the Ability of Cells to Repair Damaged DNA - Ogara, Maria Florencia (2013)
The maintenance of genomic integrity is of main importance to the survival and health of organisms which are continuously exposed to genotoxic stress. Cells respond to DNA damage by activating survival pathways consisting of cell cycle checkpoints and repair mechanisms. However, the signal that triggers the DNA damage response is not necessarily a direct detection of the primary DNA lesion. In fact, chromatin defects may serve as initiating signals to activate those mechanisms. If the modulation of chromatin structure could initiate a checkpoint response in a direct manner, this supposes the existence of specific chromatin sensors. p19INK4d, a member of the INK4 cell cycle inhibitors, plays a crucial role in regulating genomic stability and cell viability by enhancing DNA repair. Its expression is induced in cells injured by one of several genotoxic treatments like cis-platin, UV light or neocarzinostatin. Nevertheless, when exogenous DNA damaged molecules are introduced into the cell, this induction is not observed. Here, we show that p19INK4d is enhanced after chromatin relaxation even in the absence of DNA damage. This induction was shown to depend upon ATM/ATR, Chk1/Chk2 and E2F activity, as is the case of p19INK4d induction by endogenous DNA damage. Interestingly, p19INK4d improves DNA repair when the genotoxic damage is caused in a relaxed-chromatin context. These results suggest that changes in chromatin structure, and not DNA damage itself, is the actual trigger of p19INK4d induction. We propose that, in addition to its role as a cell cycle inhibitor, p19INK4d could participate in a signaling network directed to detecting and eventually responding to chromatin anomalies.